Investigation of the Effectiveness of TRIZ Invention for Enhancing Design Creativity in High School Students in China: The role played by teacher self-efficacy - Dongna, Liu; SHARUDIN@SHARADDIN, SHARUL AZIM BIN (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose – The purpose of this study was to evaluate the effectiveness of creative problem solving methodologies, such as TRIZ, in boosting design creativity in high school students in China, considering the role of the teachers’ self-efficacy in implementing such interventions. Design/methodology/approach –The study employs an experimental or quantitative research methodology to systematically assess the efficacy of the TRIZ intervention and explore the factors characterizing the integration of creative applied methodologies into educational practice. Results demonstrate a significant increase in students’ design creativity following the TRIZ intervention, as evidenced by pre- and post-intervention assessments. Findings – The study reveals a strong correlation between teacher self-efficacy and the effective implementation of TRIZ. Teachers with high self-efficacy in teaching TRIZ were more likely to create learning environments that enhanced student creativity, thereby maximizing the intervention’s impact. Conversely, teachers with lower self-efficacy showed resistance to incorporating TRIZ into their teaching practices, potentially compromising its effectiveness. This study demonstrates the significant potential of the TRIZ methodology for enhancing the design creativity of high school students in China. Research limitations– The study has limitations because of its geographical concentration on the Chinese students and teachers. Future research could look into additional regions to validate this notion. Practical implications – For effective implementation of TRIZ, teachers should prepare their teaching material that incorporates TRIZ principles systematically.